Neue Leitbilder der Raumentwicklung in Deutschland. Modernisierung der Raumordnungspolitik im Diskurs. - Aring, Jürgen; Sinz, Manfred (TH Zürich, NSL, 2006)
Der Beitrag gibt eine Einführung in die Leitbilder der Raumentwicklung in Deutschland in den Jahren 2003 bis 2006. Er legt dabei den Schwerpunkt auf die Darstellung des Erarbeitungsprozesses der neuen Leitbilder - 1. Wachstum und Innovation, 2. Öffentliche Daseinsvorsorge sichern, 3. Ressourcen bewahren, Kulturlandschaften gestalten - mit den komplementären politischen und Expertendiskursen. Es geht dabei um die Nutzung und die Rolle von "evidence" im Prozess von Politikformulierung. Rückwirkend wird im Lichte der Diskussion über "evidence-based planning" und "evidence-based policy" dargestellt, welchen Stellenwert Deskription/Analyse, Deutung/Dateninterpretation sowie Präskription/Planung für die Genese der Leitbilder gehabt haben. goj/difu

Under the German Spatial Planning Act, so-called guiding principles of spatial development are "soft" instruments for coordinating the aims and measures of spatial development policy. Against the backdrop of globalization and demographic change, Germany developed new guiding principles between 2003 and 2006. First, the paper presents the three guiding principles: growth and innovation, safeguarding services of general interest, and preserving resources and shaping cultural landscapes. It then explains the most important relevant planning policy innovations. What follows is an account of the genesis of the guiding principles. The discursive approach was open for external input. At the same time, interim results and propositions were being, tested over an over again. Retrospectively, it is possible to distinguish two related processes: a professional-scientific discourse and a political discourse. It was only the interaction between the two that made t c development of innovative and at the same time politically acceptable guiding, principles of spatial development possible. The paper examines the process of formulating guiding principles within the context of the discussion about evidence-based planning and arrives at the conclusion that the process can be described as "evidence-driven". difu
Keywords: Raumordnung; Politikwissenschaft; Raumplanung; Planungstheorie; Raumordnungspolitik; Leitbild; Raumentwicklung; Planungswissenschaft